Synthesis of Core-Shell Composite of Conductive Polymeric Materials onto Silica Using Supercritical Carbon Dioxide. (2020) - Huang, Ssu-Hao; Chen, Pei-Hua; Chen, Yan-Ping; Tang, Muoi
ABSTRACT: The polymerization of 3, 4-ethylenedioxythiophene (EDOT) onto nanosilica (SiO2 ) was synthesized in this study by using supercritical carbon dioxide (SCCO2 ). With the addition of dopants of p-toluenesulfonic acid (p-TSA) or decylbenzene sulfonic acid (DBSA), the PEDOT/SiO2 composite became conductive. The product was characterized by FTIR spectroscopy and the core-shell structure was confirmed through the TEM images. The electrical properties were analyzed by UV-vis absorbance and four-point probe measurement. DBSA is shown as the better dopants with the molar ratio (DBSA/EDOT) of 0.2 at the reaction time of 48 hours. The maximum coating percentage is 63 wt% under the optimal operation conditions at 40 o C and 280 bar. The conductivity is tuned up to 6.6×10 -2 S/cm after the coating process.